Serum sex hormone-binding globulin, a determinant of cardiometabolic disorders independent of abdominal obesity and insulin resistance in elderly men and women - Onat, Altan; Hergenc, Guelay; Karabulut, Ahmet; Albayrak, Sinan; Can, Guenay; Kaya, Zekeriya (W B SAUNDERS CO-ELSEVIER INC, 2007)
Serum sex hormone-binding globulin (SHBG) is related to cardiometabolic disorders; but whether or not this relationship is purely secondary to hyperinsulinemia and/or obesity, which down-regulates SHBG, is unknown. The aim of the study was to investigate the association of SHBG and total testosterone with atherogenic dyslipidemias, metabolic syndrome (MS), and diabetes among predominantly elderly Turkish adults. After appropriate exclusions, 777 randomly selected male and female subjects with available measurements of both variables were eligible and were analyzed cross-sectionally, with diabetic subjects analyzed separately. Free testosterone was calculated. Metabolic syndrome was identified by the modified criteria of the Adult Treatment Panel III. Metabolic syndrome was identified in half the sample,,which had a median age of 58 years. The odds of low SHBG concentrations (<45 nmol/L in men, <55 nmol/L in women) for the likelihood of 2 types of dyslipidemias, MS, and diabetes were examined by regression analyses in standard models including age, smoking status, presence of abdominal obesity, and insulin resistance (homeostasis model assessment of insulin resistance). In both sexes, low SHBG was associated independently with high triglyceride/low high-density lipoprotein dyslipidemia and with MS, at significant 2.2- to 4.5-fold odds ratios, independent of waist circumference or homeostasis model assessment of insulin resistance index. Low SHBG among women was additionally associated with the likelihood of hypertriglyceridemia with elevated apolipoprotein B and-at borderline significance-with that of diabetes, again when adjusted for the same confounders. In an elderly population with prevalent MS, low SHBG levels significantly associate with high triglyceride/low high-density lipoprotein dyslipidemia, MS, and, in women alone, diabetes and a dyslipidemia marking small dense low-density lipoprotein particles, all independent of abdominal obesity and insulin resistance. Low SHBG may be an important independent factor for cardiometabolic risk, particularly in women. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: MIDDLE-AGED MEN; METABOLIC SYNDROME; STEROID-HORMONES; CARDIOVASCULAR-DISEASE; TURKISH WOMEN; RISK; TESTOSTERONE; GLUCOSE; PROFILE; LIPOPROTEIN; Endocrinology & Metabolism